Quantum algebras, q-polynomials of Kravchuk and q-functions of Kravchuk-Meixner - Groza , V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Addition and multiplication theorems are proved for Kravchuk q-polynomials by means of methods from the theory of representations of the quantum algebras U_q (su_2) and U_q(su_1,1), and Kravchuk-Meixner q-functions are introduced and are shown to be orthogonal on the set of integers.